The European Lepidocyrtus lanuginosus group (Collembola: Entomobryidae), definition and description of a new species from Spain - Mateos, Eduardo (Zootaxa, 2012)
The Lepidocyrtus lanuginosus group is formed by the species L. lanuginosus and L. cyaneus, which can be differentiated by the body color pattern. In the present paper several populations of these two species from the Northeastern Iberian Peninsula have been studied. This study has allowed the detection of chaetotaxic and morphological differences distinguishing the two mentioned species. Also the description of the new species L. bicoloris has been made (also characterized by the body color pattern), as well as a redefinition of the European Lepidocyrtus lanuginosus group.